Evaluation of Signal Level Distribution in 5G Radio Relay Transmissions - Teodor Iliev; Ivaylo Stoyanov; Grigor Mihaylov; Alina Fazylova; Maria S. Papadopoulou (Engineering Proceedings, 2023)
The rapid emergence of the 5G networks has posed a number of new planning problems, which should be carefully analyzed to optimize the installation of the new technologies and to integrate them into the existing mobile network. The main planning objectives are to build up a network satisfying the expected traffic demands in its various sections, in compliance with the performance quality targets suggested by international committees International Telecommunication Union (ITU), Comité Consultatif International pour la Radio (CCIR), etc. The following paper discusses some of the main aspects which should be evaluated in the planning stage of 5G radio relay transmission, such as traffic capacity, propagation problems, and interference problems.